Pengaruh Ketepatan Waktu Publikasi t aporan Keuangan tcrhadap Cumulative Abnormal Return (Car) Perusahaan Go Publik di Indonesia - Togu Parulian Togatorop; Umi Murtini (Fakultas Bisnis UKDW, 2010)
This research is aimed at evaluating the effect of on-time publication of financial rryorts to Bapepam on the cttmulative abnormal return. The ianples were-the manufacture companies listed in BEI (Indonesia Stock ExchongQ and their respecfive profits durtuS 2004-2007. The result of the auluation prwes that on-time publication of financial reports has an influence on the cumulative abnormal return.Keywords : on-time, c'tnnalative abnormal return